Nature alive : essays on the emergence and evolution of living agents - Scarfe, Adam Christian, 1972- (Cambridge Scholars Publishing, 2018)
"This volume pays homage to Alfred North Whitehead's (1861-1947) profound lecture and essay entitled "Nature Alive," which was one of his most mature expressions of his process-relational metaphysics - a holistic conceptual framework that renders vivid the dynamic character of the natural world and the intrinsic purposiveness, selective agency, and creativity of living organisms. Inspired by, but not beholden to, Whitehead's process metaphysical "lens," the contributors to this volume bring a multiplicity of philosophical orientations to the table in challenging the mechanistic and reductionistic neo-Darwinian paradigm that is still dominant today in the life sciences. Mechanistic neo-Darwinism views nature and living organisms as "machines," namely, as networks of externally related and linear causal "switches," "dials," "levers," "pulleys," and "gears," that are "at the ready" for technological and biotechnological manipulation. Seeking a conceptual framework and a language that are more adequate to the study of the natural world and of living creatures than the mechanistic orientation, the contributors to this volume explore several of the "New Frontiers of Biology," which are areas of biology whose findings to some extent go beyond the explanatory confines of the Modern Synthesis of natural selection and genetics. Most notably, emergence theory, the theory of organic selection, epigenetics, homeostasis, chronobiology, and autopoiesis research can provide us with key insights that can assist us in explaining how living agents emerged, including the evolutionary origins of mentality, consciousness, and mind. Moreover, attention to the "New Frontiers of Biology" can serve to "re-enchant" our understanding of the natural world and to prevent ecological devastation, through a restoration to objectivity of notions such as "intrinsic purposiveness," "selective agency," "creativity," and "intrinsic value."--